2008
DOI: 10.1118/1.3013556
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of a commercial biologically based IMRT treatment planning system

Abstract: A new inverse treatment planning system (TPS) for external beam radiation therapy with high energy photons is commercially available that utilizes both dose-volume-based cost functions and a selection of cost functions which are based on biological models. The purpose of this work is to evaluate quality of intensity-modulated radiation therapy (IMRT) plans resulting from the use of biological cost functions in comparison to plans designed using a traditional TPS employing dose-volume-based optimization. Treatm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
78
1
4

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 101 publications
(85 citation statements)
references
References 60 publications
2
78
1
4
Order By: Relevance
“…A study conducted by Qi et al [5] concluded that "the use of biological models in treatment planning optimization can generate IMRT plans with significantly improved normal tissue sparing with similar or slightly increased dose heterogeneity in the target." Considering the improvements in OAR doses using Monaco's biological cost functions, confirmed both in this study and in an independent evaluation by Semenenko et al [8], there may be scope in the future to dose escalate PPRT since both five-year biochemical relapse-free survival and disease-free survival were significantly higher (83% versus 71% ( = 0.001) and 94% versus 88% ( = 0.005), resp.) in a cohort of patients who received 70 Gy [9].…”
Section: Discussionsupporting
confidence: 62%
“…A study conducted by Qi et al [5] concluded that "the use of biological models in treatment planning optimization can generate IMRT plans with significantly improved normal tissue sparing with similar or slightly increased dose heterogeneity in the target." Considering the improvements in OAR doses using Monaco's biological cost functions, confirmed both in this study and in an independent evaluation by Semenenko et al [8], there may be scope in the future to dose escalate PPRT since both five-year biochemical relapse-free survival and disease-free survival were significantly higher (83% versus 71% ( = 0.001) and 94% versus 88% ( = 0.005), resp.) in a cohort of patients who received 70 Gy [9].…”
Section: Discussionsupporting
confidence: 62%
“…In our clinic, some of the IMRT beams from the presented plans were verified using a two-dimensional detector array (15). Gamma analyses showed good agreement between the dose distributions calculated using the Monaco TPS and the measured distributions.…”
Section: Discussionmentioning
confidence: 94%
“…In the Monaco TPS, the plans were configured using biological and physical constraints (13)(14)(15). For the PTV, a Poisson cell kill model was used combined with a quadratic overdose constraint to avoid hot spots inside the PTV.…”
Section: Treatment Plansmentioning
confidence: 99%
“…Several treatment planning systems have been developed that incorporate gEUD cost functions for IMRT optimization. Previous investigations have confirmed the effectiveness of gEUD cost functions for plan optimization 6, 7, 8. For more complex plans, more iterations are required because many parameters need to be finely tuned for dose–volume (DV)‐based objective functions.…”
Section: Introductionmentioning
confidence: 95%